To solve the expression 3x(9x - 4y)(9x + 4y), we can use the distributive property twice.
First, distribute 3x to both terms inside the parentheses:
3x * 9x = 27x^2
3x * (-4y) = -12xy
Now, distribute 3x to both terms inside the second set of parentheses:
3x * 9x = 27x^2
3x * 4y = 12xy
Combining like terms, we have:
27x^2 - 12xy + 27x^2 + 12xy
The -12xy and +12xy terms cancel each other out, so we're left with:
27x^2 + 27x^2
Now, add the two like terms together:
27x^2 + 27x^2 = 54x^2
Therefore, 3x(9x - 4y)(9x + 4y) simplifies to 54x^2.
3x (9x - 4y) (9x + 4y)
1 answer